2007
DOI: 10.2174/1874110x00701010047
|View full text |Cite
|
Sign up to set email alerts
|

EMOTION-II Model: A Theoretical Framework for Happy Emotion as a Self-Assessment Measure Indicating the Degree-of-Fit (Congruency) between the Expectancy in Subjective and Objective Realities in Autonomous Control Systems

Abstract: Abstract:The second phase of the "EMOTION-II" model ("Emotional Model Of the Theoretical Interpretations Of Neuroprocessing") introduces the theoretical framework for the evolution of emotion as an internal measure of modeling errors (discrepancy signals) for assessing the degree-of-fit (congruency) between internal model and external world in autonomous control systems. It is derived based on the inevitable real-world consequence that modeling errors often occur in the internal model that represents the exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…The next phase of the "EMOTION-II" model presented in the next paper [5] will establish the "internal model" needed for the representation of the external world for an autonomous control system to function, and provide the derivation of principles for the emergence of happy/unhappy emotions for self-assessment and consistency-check when comparing the discrepancy between the expectancy in objective and subject realities (not just sensation, as in EMOTION-I).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The next phase of the "EMOTION-II" model presented in the next paper [5] will establish the "internal model" needed for the representation of the external world for an autonomous control system to function, and provide the derivation of principles for the emergence of happy/unhappy emotions for self-assessment and consistency-check when comparing the discrepancy between the expectancy in objective and subject realities (not just sensation, as in EMOTION-I).…”
Section: Discussionmentioning
confidence: 99%
“…It addresses the emergence of the "feel" of sensation for increasing the chance of survival as the first step in internal pre-processing of emotions. The subsequent paper [5] will focus on the second phase in developing the minimal set of basic emotions for this model: EMOTION-II. It addresses the emergence of a metric for assessing the accuracy of the internal model.…”
Section: Emotion-i Modelmentioning
confidence: 99%
“…A theoretical emotional model was proposed previously to describe how emotion is evolved to increase the survivability of an organism by providing the feedback to correct for any discrepancy between the internal predictions and the actual outcomes [1,2]. Using a set of minimal assumptions, it can be shown that the computations in emotional processing involve the assessment of the disparity between the internally generated world model (subjective reality) and the actual real world (objective reality) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Toward this goal to examine the functional role of emotions in survival, a neurobiological model had been developed to explore the computations involved in emotional processing [1,2]. Using a minimal assumption approach, it can be shown that an objective model of emotion can be quantified using basic principles of survival [1,2].…”
Section: Introductionmentioning
confidence: 99%